2015
DOI: 10.4149/bll_2015_003
|View full text |Cite
|
Sign up to set email alerts
|

DNA typing of HLA-A, -C, -B, AND -DRB1 in the children with autism in the Republic of Macedonia

Abstract: Abstract:In the present study, we report the fi rst DNA analysis of HLA class I and class II alleles in Macedonian autistic subjects. We have analyzed the HLA-A, -C, -B, DRB1 genotypes of 35 autistic patients, and 98 healthy unrelated Macedonians (control group). HLA DNA typing of class I genes was performed using a Reverse Line Strip method (RLS), and the Sequencing Based Typing method (SBT) was used for typing of class II genes. In the autistic subjects for HLA-A locus 14 alleles have been identifi ed with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…Among HLA-DRB alleles, we only demonstrated over-presentation of DRB1*01 in ASD patients compared with controls but 95% CI values include OR =1, which disapproves the results. HLA-DRB1*01 has been previously shown to be associated with rheumatoid arthritis in Syrian population16 and with ASD in Macedonia 17. Although we could not detect any association between DRB1*04 allele and ASD, the role of this allele in ASD susceptibility has been shown in multiple studies.…”
Section: Discussioncontrasting
confidence: 80%
“…Among HLA-DRB alleles, we only demonstrated over-presentation of DRB1*01 in ASD patients compared with controls but 95% CI values include OR =1, which disapproves the results. HLA-DRB1*01 has been previously shown to be associated with rheumatoid arthritis in Syrian population16 and with ASD in Macedonia 17. Although we could not detect any association between DRB1*04 allele and ASD, the role of this allele in ASD susceptibility has been shown in multiple studies.…”
Section: Discussioncontrasting
confidence: 80%
“…Several studies have revealed links between HLA and ASD, where autistic children were found to have a higher frequency of HLA-DRB1*11 allele and lower frequency of HLA-DRB1*03 allele [ 40 ]. Several other investigators reported on an association between HLA and ASD in different populations including Caucasian [ 41 45 ], Thai [ 46 ], Saudi Arabian [ 47 ], and Chinese [ 48 ]. An interesting association of HLA-G polymorphism with ASD, likely a consequence of prenatal immune activation, was reported by Guerini et al [ 49 ].…”
Section: Immunological Background Of Asdmentioning
confidence: 99%
“…Hence, it is believed that understanding these alterations will help us to identify ASD in an early stage and initiate a better treatment. alleles were selected in another study, but none of these alleles showed consistent results (16). Al-Hakbany et al (28) could only find HLA-B * 07 significantly associated with ASD in his case-control study, the extended haplotype HLA-A * 02-B * 07 was significantly higher in ASD compared to controls.…”
Section: Discussionmentioning
confidence: 92%